2018
DOI: 10.1101/lm.046870.117
|View full text |Cite
|
Sign up to set email alerts
|

Highway to hell or magic smoke? The dose-dependence of Δ9-THC in place conditioning paradigms

Abstract: The prerequisites for responsible cannabis use are at the heart of current inquiries into cannabis decriminalization by policy makers as well as academic and nonacademic stakeholders at a global scale. Δ-tetrahydrocannabinol (Δ-THC), the prime psychoactive compound of the , as well as cannabimimetics that resemble the pharmacological properties and psychological effects of Δ-THC, lend themselves handsomely to the preclinical scrutiny of reward-related behavior because they carry marked translational value. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 88 publications
(96 reference statements)
2
22
0
Order By: Relevance
“…Furthermore, Bedse et al [147] demonstrated in mice that the 2-AG depletion-induced anxiety-like behavior after stress exposure was counteracted by the administration of 0.25 mg/kg THC. Overall, these findings confirm the bidirectional effects of THC on anxiety, despite the varying dose range associated with anxiolytic and anxiogenic effects [148]. Of note, at doses ranging from 3.0 to 10 mg/kg in rats, and from 10 to 20 mg/kg in mice, THC also produced sedative-like effects [143].…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, Bedse et al [147] demonstrated in mice that the 2-AG depletion-induced anxiety-like behavior after stress exposure was counteracted by the administration of 0.25 mg/kg THC. Overall, these findings confirm the bidirectional effects of THC on anxiety, despite the varying dose range associated with anxiolytic and anxiogenic effects [148]. Of note, at doses ranging from 3.0 to 10 mg/kg in rats, and from 10 to 20 mg/kg in mice, THC also produced sedative-like effects [143].…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, there are contradictory results, because i.p. Δ 9 -THC administration could promote either conditioning place preference (CPP) or even aversion in a dose-dependent manner (Kubilius et al, 2018;Manwell et al, 2014;Murray and Bevins, 2010). By contrast, more consistent results have been reported using WIN55,212-2, since it induced CPP (Castañé et al, 2004;Manzanedo et al, 2010) probably due to its higher affinity for CB1 and CB2 receptors than Δ 9 -THC (Thomas et al, 1998).…”
Section: Introductionmentioning
confidence: 95%
“…In rodents, some studies have achieved the self-administration of cannabinoids, using intravenous Δ 9 -THC (Spencer et al, 2018), vaporized Δ 9 -THC (Freels et al, 2020), or intravenous R-(+)-[2,3-Dihydro-5-methyl-3-(4-morpholinylmethyl)pyrrolo[1,2,3-de]-1,4-benzoxazin-6-yl]-1napthalenylmethanone mesylate (WIN55,212-2), a synthetic cannabinoid receptor agonist (Kirschmann et al, 2017;Mendizábal et al, 2006). The low reliability of the cannabinoids self-administration could be due to the low rewarding effects of Δ 9 -THC observed in the conditioning place preference paradigm (Kubilius et al, 2018). Indeed, there are contradictory results, because i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the dose‐dependent nature of cannabinoids’ reward‐related psychological effects can not only bear implications for explaining and treating motivational disorders, but also for cannabis decriminalization (Kubilius et al. ). Leaving aside that the Islamic permissibility of cannabis use can be debated in and of itself, such research potentially conflicts with Islamic legal maxims and precepts if its rationale is to simply push cannabis decriminalization policies for recreational cannabis use.…”
Section: Islamic Cognitive Theoriesmentioning
confidence: 99%